Implementation of the Outdoor Study Method to Improve Natural Science Learning Outcomes for Class V Students - Selian, Auliantika; Prihatin, Relly (Indonesian Journal of Learning and Instructional Innovation, 2025)
This study aims to describe the application of the outdoor study method to improve the learning outcomes of natural science students in grade V of SD Negeri Kleco I Surakarta. This research was carried out at SD Negeri Kleco I Surakarta. The research subjects consisted of 20 students who had intermediate academic abilities. This research is a classroom action research that is carried out in a cyclical manner. Each cycle consists of planning, implementation, observation, and reflection steps. The data collection techniques used are observation techniques and data analysis techniques. In this study, qualitative and quantitative data analysis techniques are used. For qualitative data descriptions, they can be analyzed using observation sheets, while quantitative descriptions are carried out with tests that have been given. The learning outcomes in cycle 1 were 71.67% with a good category and in cycle 2 an average score increase of 78.33% was obtained with a good category. Likewise with the completeness of student learning, in cycle 1 there were 13 students or 83.33% who completed and in cycle 2, 100% of students were obtained. It can be concluded that the application of the outdoor study method to improve the learning outcomes of natural science students in grade V of SD Negeri Kleco I Surakarta is good.